Assessing the Effectiveness of Creative Problem-Solving Learning on Mathematical Creativity and Communication Across Varying Self-Regulation Levels - Pramesti, Getut; Mardaningtyas, Falerinda (Jurnal Pendidikan MIPA, 2025)
This study aims to determine which learning model, Creative Problem Solving (CPS) or direct learning, and which level of self-regulated learning, high, medium, or low, is better for increasing mathematical creative thinking and mathematical communication skills. The research method used is quantitative research with a quasi-experimental design. The sampling technique employed cluster random sampling, resulting in the selection of Class VII D, which was assigned the direct instruction model, and Class VII E, which was assigned the CPS model. Data analysis in this study utilized multivariate analysis of variance. The results of the study indicate that, in terms of mathematical creative thinking and mathematical communication skills, the CPS learning model is better than the direct learning model, students with high self-regulated learning are better than students with moderate self-regulated learning, and both are better than students with low self-regulated learning. Additionally, there was no interaction between the learning model and students' self-regulated learning. There are still limited studies discussing the application of the CPS model on mathematical creative thinking and mathematical communication skills from the perspective of self-regulated learning so that this study can contribute to the existing literature on this topic.    Keywords: creative problem solving, self-regulated learning, mathematical creative thinking skill, mathematical communication skill.